Electrically tunable steganographic nano-optical coatings - Prabhathan, Patinharekandy (2023)
Thin film coatings with tunable colors have a broad range of applications, from solid-state reflective displays to steganography. Here, we propose a novel approach to chalcogenide phase change material (PCM)-incorporated steganographic nano-optical coatings (SNOC) as thin film color reflectors for optical steganography. The proposed SNOC design combines a broad-band and a narrow-band absorber made up of PCMs to achieve tunable optical Fano resonance in the visible wavelength, which is a scalable platform for accessing the full-color range. We demonstrate that the line width of the Fano resonance can be dynamically tuned by switching the structural phase of PCM from amorphous to crystalline, which is crucial for obtaining high-purity colors. For steganography applications, the cavity layer of SNOC is divided into an ultralow loss PCM and a high index dielectric material with identical optical thickness. We show that electrically tunable color pixels can be fabricated using the SNOC on a microheater device.